Transforming the development landscape : the role of the private sector - Brainard, Lael. (Washington, D.C. : Brookings Institution Press, 2006)
Private sector activity is crucial for development. It shapes the investment climate, mobilizes innovation and financing in areas such as global health, and can either cause or mitigate social and environmental harm. Yet so far, the international development debate has not focused on the role of the private sector. This volume-written by members of the private sector, philanthropic organizations, and academia-investigates ways to galvanize the private sector in the fight against global poverty. Using a bottom-up approach, they describe how the private sector affects growth and poverty alleviati.
The private sector in the fight against global poverty / Lael Brainard and Vinca LaFleur -- Unleashing entrepreneurship / Warrick Smith -- Leveraging the development impact of business in the fight against global poverty / Jane Nelson -- Blended value investment and a living return / Timothy Freundlich -- Should governments and aid agencies subsidize small firms? / Ross Levine -- Venture capital for development / Alan J. Patricof and Julie E. Sunderland -- Innovative financing options and the fight against global poverty : what's new and what next? / David de Ferranti -- 2 + 2 = 5 : a pragmatic view of partnerships between official donors and multinational corporations / Larry Cooley -- Financing for global health / Rajiv Shah and Sylvia Mathews.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: Economic development projects -- Developing countries -- Finance; Free enterprise -- Developing countries; Business enterprises -- Developing countries; Investments, Foreign -- Developing countries; Economic development projects -- Developing countries; Projets de développement économique -- Pays en voie de développement.; Libre entreprise -- Pays en voie de développement.; Entreprises -- Pays en voie de développement.; Investissements étrangers -- Pays en voie de développement.; POLITICAL SCIENCE -- Public Policy -- Economic Policy; BUSINESS & ECONOMICS -- Government & Business; BUSINESS & ECONOMICS -- Development -- Economic Development; BUSINESS & ECONOMICS -- Development -- Business Development; BUSINESS & ECONOMICS -- Structural Adjustment; BUSINESS & ECONOMICS -- Development -- General; Economic development projects; Business enterprises; Economic development projects -- Finance; Free enterprise; Investments, Foreign; Developing countries; Wirtschaftsentwicklung; Privatwirtschaft; Entwicklungsländer